Reimbursement models to tackle market failures for antimicrobials: Approaches taken in France, Germany, Sweden, the United Kingdom, and the United States. Issue 3 (March 2021) - Gotham, Dzintars; Moja, Lorenzo; van der Heijden, Maarten; Paulin, Sarah; Smith, Ingrid; Beyer, Peter
Highlights: New antimicrobials are urgently needed, but the pipeline of products is limited. Changes in how antimicrobials paid for may help address this. We compared reimbursement interventions across France, Germany, Sweden, the UK, the US. Interventions in France, Germany, and the US, are relatively modest. Sweden and the UK are piloting entirely novel reimbursement mechanisms for antimicrobials. Abstract: Introduction: The pipeline of new antibacterials remains limited. Reasons include low research investments, limited commercial prospects, and scientific challenges. To complement existing initiatives such as research grants, governments are exploring policy options for providing new market incentives to drug developers. Materials and methods: Reimbursement interventions for antibacterials in France, Germany, Sweden, US, and UK were reviewed and analysed by the authors. Results: In France, Germany, and the US, implemented interventions centre on providing exceptions in cost-containment mechanisms to allow higher prices for certain antibacterials. In the US, also, certain antibacterials are granted additional years of protection from generic competition (exclusivity) and faster regulatory review. The UK is piloting a model that will negotiate contracts with manufacturers to pay a fixed annual fee for ongoing supply of as many units as needed. Sweden is piloting a model that will offer manufacturers of selected antibacterials contracts that would guarantee a minimum annual revenue. A similar model of guaranteed minimal annual revenues is under consideration in the US (PASTEUR Act). Conclusions: The UK and Sweden are piloting entirely novel procurement and reimbursement models. Existing interventions in the US, France, and Germany represent important, but relatively minor interventions. More countries should explore the use of novel models and international coordination will be important for 'pull' incentives to be effective. If adopted, the PASTEUR legislation in the US would constitute a significant 'pull' incentive.